2012
DOI: 10.3402/gha.v5i0.15638
|View full text |Cite
|
Sign up to set email alerts
|

The role of information communication technology (ICT) towards universal health coverage: the first steps of a telemedicine project in Ethiopia

Abstract: BackgroundEighty-five per cent of the Ethiopian population lives in remote areas, without access to modern health services. The limited health care budget, chronic shortage of health care workers and lack of incentives to retain those in remote areas further jeopardize the national health care delivery system. Recently, the application of information communication technology (ICT) to health care delivery and the use of telemedicine have raised hopes.ObjectiveThis paper analyzes the challenges, failures and suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
128
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 15 publications
0
128
0
1
Order By: Relevance
“…For teleradiology to be effective, the standard quality of radiology services provided must be ensured [5]. A major technical consideration for many countries is low bandwidth, slow Internet connection and high Internet service charges [3]. Areas of the developing world continue to have data transmission speeds of 10 kbps vs. the 1 mbps available in developed countries [6].…”
Section: Technical Barriersmentioning
confidence: 99%
See 4 more Smart Citations
“…For teleradiology to be effective, the standard quality of radiology services provided must be ensured [5]. A major technical consideration for many countries is low bandwidth, slow Internet connection and high Internet service charges [3]. Areas of the developing world continue to have data transmission speeds of 10 kbps vs. the 1 mbps available in developed countries [6].…”
Section: Technical Barriersmentioning
confidence: 99%
“…Many tele-reading programs use screen-film images converted into digital files via digital cameras, scanners or specialized digitizers. An Ethiopian tele-reading program found that taking photographs of radiographs with a regular camera, using natural light on a white glared window, produced good-quality images, and this was proposed as good solution for areas in which light boxes are not available and a stable power source is an issue [3]. Such systems are feasible, but there is limited opportunity to improve the image quality if the primary radiograph is poor [1].…”
Section: Technical Barriersmentioning
confidence: 99%
See 3 more Smart Citations